Pelatihan Pengembangan Konten Pemasaran Melalui Media Sosial Untuk Membantu Perkembangan UMKM Di Kelurahan Keputih - Rahma Febriana; Riko Setya Wijaya; M. Taufiq (STIKes Ibnu Sina Ajibarang, 2023)
MSMEs play an important role in the Indonesian economy. Therefore, the development and progress of MSMEs is very important. One of the efforts to increase the development of MSMEs is through promotional strategies by creating attractive and innovative marketing content. In addition, MSME players must also be able to utilize social media as an effective and efficient promotion and sales media. Both of these are good strategies, especially in the current digitalization era. However, after conducting a field survey, it was found that MSME players in the Keputih village area did not understand how to create content and utilize social media properly. Therefore, the group 74 KKN-T MBKM UPN